Pengaruh Citra Merek, Kualitas Produk Dan Promosi Terhadap Keputusan Pembelian Produk Pada PT Trimitra Warna Jaya - Raphael Romeo Lenardo; Inda Sukati (Komunitas Dosen Indonesia, 2023)
The purpose of this research is to examine the effect of brand image, product quality and promotion on product purchasing decisions at PT Trimitra Warna Jaya. The basic method used in this research is quantitative research method survey research is an option in this study as well as the use of questionnaires in the process of collecting survey data obtained from information from respondents. The population used in the researchers' research was consumers who had purchased Asian paints at PT Trimitra Warna Jaya in the period October 2022 to October 2023. Determining the size of the sample can be done using the Cochran formula. Methods of data analysis were used through validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, analysis of the coefficient of determination (R2), t test and f test. The results of the study show that brand image has a t-count of 1.565 <1.98498 and 0.121 > 0.05 that there is no partial positive and significant influence of brand image on consumer purchasing decisions at PT Trimitra Warna Jaya. Then on product quality, it has a t count of 3.145 > 1.98498 and 0.002 <0.05 which shows a partial positive and significant influence on product quality on consumer purchasing decisions at PT Trimitra Warna Jaya. Then the promotion has a t count of 6.029 > 1.98498 and 0.000 <0.05 which shows that promotion has a partial positive and significant effect on consumer purchasing decisions at PT Trimitra Warna Jaya. The results simultaneously found 36.740 > 2.70 and a significance of 0.000 <0.05, so brand image, product quality and promotion of consumer purchasing decisions at PT Trimitra Warna Jaya